2018
DOI: 10.1111/jcpt.12682
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between SLCO 1B1 polymorphisms and lipid‐lowering response to simvastatin therapy in Thai hypercholesterolaemic patients

Abstract: SLCO1B1 c.388A>G, c.521T>C and g.89595T>C polymorphisms may not be useful as genetic markers of lipid-lowering response to simvastatin therapy in Thai hypercholesterolaemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…According to the studies, investigations of parts area about SLCO1B1 are showed clearly: Geek, German, Indian (North) and Macedonian manifest the relatively lower rate of G allele in G388A, less than 50%, whereas Thailand and Chinese population show higher than former, generally above 70%. By contrast, the allele frequency exhibits little difference in SLCO1B1 gene 521T>C polymorphism (Dendramis, 2011;Giannakopoulou et al, 2014;Hubacek et al, 2015;Kaewboonlert et al, 2018;Melo et al, 2015;Meyer zu Schwabedissen et al, 2015;Mladenovska et al, 2017;Ramakumari et al, 2018;Treenert et al, 2018;Wu et al, 2018). In this study, the mutation allele frequency of SLCO1B1 gene 388A>G and 521T>C were 74.89% (74.64% in male and 75.30% in female) and 11.54% (12.14% in male and 10.57% in female) respectively.…”
Section: Discussionmentioning
confidence: 51%
“…According to the studies, investigations of parts area about SLCO1B1 are showed clearly: Geek, German, Indian (North) and Macedonian manifest the relatively lower rate of G allele in G388A, less than 50%, whereas Thailand and Chinese population show higher than former, generally above 70%. By contrast, the allele frequency exhibits little difference in SLCO1B1 gene 521T>C polymorphism (Dendramis, 2011;Giannakopoulou et al, 2014;Hubacek et al, 2015;Kaewboonlert et al, 2018;Melo et al, 2015;Meyer zu Schwabedissen et al, 2015;Mladenovska et al, 2017;Ramakumari et al, 2018;Treenert et al, 2018;Wu et al, 2018). In this study, the mutation allele frequency of SLCO1B1 gene 388A>G and 521T>C were 74.89% (74.64% in male and 75.30% in female) and 11.54% (12.14% in male and 10.57% in female) respectively.…”
Section: Discussionmentioning
confidence: 51%
“…The comparison of our results with those of Hapmap Project [12] and other studies [4,5,11,13] is illustrated in Table 4. The genotype and allele frequencies of Turkish population demonstrated prominent dissimilars when compared to East Asian and Southeast ancestry.…”
Section: Discussionmentioning
confidence: 61%
“…They observed that no significant was distinction among three groups for genotype frequencies of SLCO1B1, and also there was no relationship between rs4363657 polymorphism in SLCO1B1 and risk of myalgia/myopathy in low doses of statin-treated Czech patients. In addition, Kaewboonlert et al [5] reported that there was no relationship between SLCO1B1 g.89595 T>C polymorphism and lipid-lowering response to 3 and 12 months of 20 or 40 mg/day simvastatin treatment in Thai patients with hypercholesterolaemia (n=391). It has been concluded that in lipid-lowering response to simvastatin treatment in Thai patients with hypercholesterolaemia, SLCO1B1 g.89595 T>C polymorphism should not be employed as the genetic markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations